Spatial Neglect Midline Diagnostics From Virtual Reality and Eye Tracking in a Free-Viewing Environment - Hougaard, Bastian I.; Knoche, Hendrik; Jensen, Jim; Evald, Lars (Frontiers in Psychology, 2021)
Purpose: Virtual reality (VR) and eye tracking may provide detailed insights into spatial cognition. We hypothesised that virtual reality and eye tracking may be used to assess sub-types of spatial neglect in stroke patients not readily available from conventional assessments. Method: Eighteen stroke patients with spatial neglect and sixteen age and gender matched healthy subjects wearing VR headsets were asked to look around freely in a symmetric 3D museum scene with three pictures. Asymmetry of performances was analysed to revealed group-level differences and possible neglect sub-types on an individual level. Results: Four out of six VR and eye tracking measures revealed significant differences between patients and controls in this free-viewing task. Gaze-asymmetry between-pictures (including fixation time and count) and head orientation were most sensitive to spatial neglect behaviour on a group level analysis. Gaze-asymmetry and head orientation each identified 10 out of 18 (56%), compared to 12 out of 18 (67%) for the best conventional test. Two neglect patients without deviant performance on conventional measures were captured by the VR and eyetracking measures. On the individual level, five stroke patients revealed deviant gaze-asymmetry within-pictures and six patients revealed deviant eye orientation in either direction that were not captured by the group-level analysis. Conclusions: This study is a first step in using VR in combination with eye tracking measures as individual differential neglect subtype diagnostics. This may pave the way for more sensitive and elaborate sub-type diagnostics of spatial neglect that may respond differently to various treatment approaches.